Geographical Analysis of The Expansion of The Area and Obstacles in Front of The City of Ankawa: A Study in The Geography of The City - Mudhafar Ahmed Rasool; Lozan Hasam Abdulrahman; Zerin Star Ibrahim (QALAAI ZANIST JOURNAL, 2023)
The phenomenon of cold urban expansion is considered a natural phenomenon of cities. After the beginning of movement and the beginning of new cities, cities developed in an environment that was not considered their own environment Urban expansion is a natural or human factor that prevents the expansion of the city. Angawa has gone through several morphological stages. At the beginning of the formation of Angawa township, it was only a small village consisting of thirty neighborhoods, but after the rise of the administrative rank from the village became a district In the late 1980s, it became six neighborhoods. In 2000, it became seven neighborhoods with a total area of ​​202.29 hectares. In 2020, it became 12 neighborhoods with an area of ​​1,027 hectares. The main objective of this research is to identify the obstacles that hinder the development and expansion of the city The first topic is the introduction of concepts and terms and the introduction of the area of ​​research in terms of history, geography and astronomical location.The second topic consists of showing the stages of expansion of Ankawa town from 1991 to Nista. The third topic discusses the characteristics and classification of the obstacles and identifies the obstacles that hinder the dialogue The expansion of the town. Finally, the conclusions, recommendations and list of references are presented.